Iowa Birdline update, October 3, 1994 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Email of the Iowa Birdline update for October 3, 1994. Highlights of the update include sightings of a Black-throated Blue Warbler in three locations, Merlins, a Red-breasted Nuthatch, and a late Indigo Bunting. Also of note were the observations of nine Warbler species in Cedar Rapids and ten Sparrow species in Greene and Polk Counties. Also included are handwritten notes for the next week's update with sightings of seven Winter Wrens and a Peregrine Falcon. Epson - sheet feed/flatbed